A Review on the human-animal biodiversity interaction - Javier-Ninahuaman, Henry Juan (Acta Scientiarum. Animal Sciences, 2025)
Little has been studied about human-animal interaction in general; Some particular experimental and descriptive studies provide information that must be systematized. The systematic review study aims to answer, using the standard Prisma methodology, the research question: What is known about the interaction of human-animal biodiversity? It includes original open access studies, of the experimental and descriptive type that provide relevant information, extracted from the Scopus database, from 2015 to 2023, using the keyword biodiversity, until the date of October 26, 2023. The analysis of the data uses cluster analysis, and the nearest neighbor method, 19 studies were selected that show the dynamic interaction between humans and animals. The study is limited to describing interactions between humans and animals, excluding other interactions. It concludes by showing the positive and negative impacts of coexistence, the majority being negative such as predation, transmission of emerging diseases, nutritional use, behavioral changes, changes in land use and their economic and social consequences, for which laws and policies that guarantee regulated coexistence.